Edukacyjny wymiar biografii Innych, czyli czego uczy „Roman” Polańskiego? - Jakubowski , Witold (Studia Edukacyjne, 2023)
The aim of this article is to point out the educational potential of biographies of Others. Published and presented in the form of feature films and documentaries, biographies allow today’s cultural participant to “enter the world” of other people, to learn about their dramas and lived trajectories of life. “The other” here is the “bearer” of experience, who provides the viewer, in his or her biographical story, with a certain knowledge of life. Biography can be treated as a text and interpreted as such. A particularly interesting theoretical interpretation to explain the educational dimension of biography is Hans Georg Gadamer’s proposed model of hermeneutic interpretation of the text. The field of analysis in the article became the biography of Roman Polanski.